Cardioprotective Effect of Crocin Combined with Voluntary Exercise in Rat: Role of Mir-126 and Mir-210 in Heart Angiogenesis - Ghorbanzadeh,Vajihe (2017)
Abstract Background: Crocin is reported to have a wide range of biological activities such as cardiovascular protection. Recent epidemiologic studies have shown that exercise reduces cardiovascular morbidity and mortality in the general population. Objective: The aim of this study was to evaluate the effect of crocin and voluntary exercise on miR-126 and miR-210 expression levels and angiogenesis in the heart tissue. Methods: Animals were divided into 4 groups: control, exercise, crocin, and exercise-crocin. Animals received oral administration of crocin (50 mg/kg) or performed voluntary exercise alone or together for 8 weeks. Akt, ERK1/2 protein levels, miR-126 and miR-210 expression were measured in the heart tissue. Immunohistochemical method was used to detect CD31 in the heart tissue. Results: Akt and ERK1/2 levels of the heart tissue were higher in crocin treated group and voluntary exercise trained group after 8 weeks. Combination of crocin and exercise also significantly enhanced Akt and ERK1/2 levels in the heart tissue. MiR-126, miR-210 expression and CD31 in the heart increased in both crocin and voluntary exercise groups compared with control group. In addition, combination of exercise and crocin amplified their effect on miR-126 and miR-210 expression, and angiogenesis. Conclusion: Crocin and voluntary exercise improve heart angiogenesis possibly through enhancement of miR-126 and miR-210 expression. Voluntary exercise and diet supplementation with crocin could have beneficial effects in prevention of cardiovascular disease.